Notes relating to the Flora of Bhutan: XXXVII. New species and records of Orchidaceae from Bhutan and India (Sikkim) - Pearce, N.; Cribb, P. (Edinburgh Journal of Botany, 1999)
Three new species of Bhutanese orchids, Aphyllorchis sanguinea, Cheirostylis sherriffii and Hetaeria pelota, and one new Sikkimese species, Lecanorchis sikkimensis, are newly described. Their generic placement and affinities are discussed. A new combination in Cheirostylis is made for the Taiwanese Zeuxine tabiyahanensis Hayata. Records of five orchid species new to Bhutan are also presented.